EFISIENSI TEKNIS USAHATANI PADI KALIMANTAN TENGAH: PENDEKATAN STOCHASTIC FRONTIER ANALYSIS - Syahputra, Agung Rahmat; Suharno, Suharno; Rifin, Amzul (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2023)
The strategy to increase rice production is crucial to maintain food availability. The agricultural land expansion program in Central Kalimantan through the food estate program is considered an inappropriate solution considering social, environmental, and land conditions. The agricultural intensification method in Central Kalimantan is the answer to increasing the productivity of existing agricultural businesses by increasing production efficiency. This research aims to analyze the technical efficiency of lowland rice farming and the factors that influence it in Central Kalimantan province. This research used secondary data from the 2014 Rice Plantation Household Survey from the Central Statistics Agency. The data was analyzed using the stochastic frontier production function with Maximum Likelihood Estimation (MLE). The research results show that rice farming in Central Kalimantan is technically inefficient. Factors influencing the technical efficiency of rice farming are farmer age, land type, planting system, agricultural facilities, extension, farmer groups, and SLPTT participation. The low level of technical efficiency of rice farming in Central Kalimantan is an indicator that must be utilized to increase rice production so that food availability can be well-maintained.